Penegakan Hukum Terhadap Tindak Pidana Eksploitasi Seksual Yang Dilakukan Oleh Suami Terhadap Istri - Iren Manalu; Rahman Amin (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Today the crime of trafficking in persons in the form of sexual exploitation is increasingly common with various modes of operation, one of which is making the wife a commercial sex worker by her husband which can be seen in print and online media, where this can also be categorized as a crime of domestic violence. As an example of the case of the criminal act of trafficking in persons in the form of sexual exploitation committed by a husband against his wife as a commercial sex worker as stated in the Decision of the Sidoarjo District Court Number 889/Pid.Sus/2018/PN. SDA, where in its application law enforcers, especially judges in court, only apply the provisions in the law on the crime of trafficking in persons even though the actions of the accused can be applied to the provisions in other relevant laws. This research is normative legal research by studying the applicable laws and regulations related to court decisions in the cases studied. The results of the study show that law enforcement of sexual exploitation crimes committed by husbands against wives in the decision of the Sidoarjo District Court Number 889/Pid.Sus/2018/PN.SDA applies Article 2 of Law Number 21 of 2007 concerning Eradication of Trafficking Crimes People, but acts of exploitation by perpetrators and victims are bound in a legal marriage, so legally the application of the law can also apply Article 8 letter b of Law Number 23 of 2004 concerning the Elimination of Domestic Violence, so that the perpetrators can be subject to maximum legal sanctions for acts exploits that have been carried out.